Gender Factor Effects on Compliance of Statin Therapy in Hyperlipidemia Patients - Noreen Irum, Parus Saleem, Sagheer Ahmed, Rukhsana Malik, Nargis Pirya, Masood Ahmed, Irfanullah Unar, Abdul Waheed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The biggest cause of death worldwide is cardiovascular disease (CVD), which accounts for 31% of all fatalities that are officially reported each year. Hyperlipidemia is thought to be a key risk factor for CVD. Due to the lack of symptoms associated with hyperlipidemia, many patients do not feel the need to take medication. Undoubtedly, treating and managing the hypercholesterolemia and other diseases with no symptoms has been difficult for both patients and medical professionals. Methodology: Study was conducted in co-operation of department of Cardiology & Medicine PMC Hospital Nawabshah. 100 patients were registered having hyperlipidemia, included through convenience sampling technique. Two groups were made age from 31-50 years and other age from 51 to 70 years. Drug compliance was measured by using Morisky scale and detailed history by using the pre-formed proforma. Results: Result showed there was compliance of statin therapy in both genders PDC was more than 80%, but in comparison of both groups statin therapy compliance was statistically non-significant p value-0.726. Conclusion: The majority of the participants in this study who had hyperlipidemia adhered to their statin medication. The factors determining compliance revealed good adherence in the high-risk population, especially in people over 50 years old. Keywords: Gender, compliance. Statin therapy. Hyperlipidemia.